Food Insecurity Among Farmers in Rural Sri Lanka and the Perceived Impacts of COVID-19. (7th June 2021) - Singh, Nishmeet; Scott, Samuel; Olney, Deanna; Kumar, Neha; Ramani, Gayathri; Jayatissa, Renuka; Sinclair, Kate; Marshall, Quinn
Abstract: Objectives: Little is known about how the COVID-19 pandemic (C19) has affected food security and farmers' livelihoods in Sri Lanka. In this study, we assessed food security, perceived impacts of C19 and coping mechanisms to deal with these impacts. Methods: As part of a baseline survey for an evaluation of the World Food Programme's Nutrition-Sensitive Food Assistance for Assets Program in Sri Lanka, we conducted ∼1300 quantitative household phone surveys across five districts between December 2020 and February 2021. Food insecurity was assessed using the 8-item Food Insecurity Experience Scale and categorized as moderate or severe using the Rasch model. Perceived impacts of C19 and the coping mechanisms used to deal with these shocks were assessed via questionnaire. Additionally, we explored how these experiences varied by wealth quintile, highest attained education level in the household, and district. Results: Despite having had a relatively low burden of C19 cases in Sri Lanka compared to other countries, 85% of respondents in our sample reported being affected in some way by C19 or its associated control measures. Reported impacts include those on income (77% overall, 89% in lowest quintile, 62% in highest quintile) and agriculture activities (76% overall, 65% in lowest quintile, 87% in highest quintile), among others. Normal crop cultivation and harvesting was adversely impacted due to being advised to stay home (42%), being unable to purchase inputs (33%) and poor demand in the market (56%). In response to COVID shocks, about 30% of respondents in the lowest two wealth quintiles reported selling their livestock and about 20% of respondents across all wealth quintiles reported selling other assets. Half of the households interviewed were either moderately (36%) or severely (14%) food insecure. The proportion of households experiencing food insecurity varied by wealth quintile (mod: 55%-21%; sev: 27%-5%) and district (mod: 46%-29%; sev: 21%-10%). Conclusions: High levels of food insecurity and disruptions across domains such as income, asset ownership, and agriculture could have short- and long-term effects on people's health, nutrition and well-being. Control measures enacted in Sri Lanka should consider the potentially devastating effects on smallholder farmers and introduce measures to mitigate these issues in those most affected. Funding Sources: A4NH and WFP